Analisis Laba dan Arus Kas Dalam Memprediksi Financial Distress (Studi Kasus Pada Perusahaan Perbankan Yang Terdaftar di BEI Periode 2016-2018) - Dian Lestari; Debbi Chyntia Ovami; Reza Hanafi Lubis (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
This research aimed to determine the ability of profit and cash flow in predicting the financial distress at the BEI-registered banking company. This type of research was a qualitative descriptive, the technique of data collection was by observation, the data used was the financial statements for 3 years starting from 2016 until the year 2018. The variables used in this study were income, cash flows and financial distress. The results showed that a better profit variable was used in predicting the financial distress in the upcoming 1 year compared to the cash flow variable